2008
DOI: 10.1530/rep-07-0405
|View full text |Cite
|
Sign up to set email alerts
|

Glial-derived neurotrophic factor promotes ovarian primordial follicle development and cell–cell interactions during folliculogenesis

Abstract: Female fertility is determined in part by the size and development of the primordial follicle pool. The current study investigates the role of glial cell-line-derived neurotrophic factor (GDNF) in the regulation of primordial follicle development in the ovary. Ovaries from 4-dayold female rat pups were maintained in organ culture for 10 days in the absence (control) or presence of GDNF or kit ligand (KL)/stem cell factor. Ovaries treated with GDNF contained a significant increase in developing follicles, simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 76 publications
3
62
0
1
Order By: Relevance
“…Therefore, NT3 signaling to its NTRK3 receptor can occur in either a paracrine or autocrine manner in primordial follicles. This is similar to the findings for GDNF, in which autocrine signaling occurs since both GDNF and its receptor GFRα1 are localized to primordial follicle oocytes (Dole et al 2008). This is also similar to the findings in human ovaries that the neurotrophins BDNF, NT4 and their receptor NTRK2 are each expressed in both oocytes and granulosa cells in larger developing follicles, so both autocrine and paracrine signaling is possible (Harel et al 2006).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, NT3 signaling to its NTRK3 receptor can occur in either a paracrine or autocrine manner in primordial follicles. This is similar to the findings for GDNF, in which autocrine signaling occurs since both GDNF and its receptor GFRα1 are localized to primordial follicle oocytes (Dole et al 2008). This is also similar to the findings in human ovaries that the neurotrophins BDNF, NT4 and their receptor NTRK2 are each expressed in both oocytes and granulosa cells in larger developing follicles, so both autocrine and paracrine signaling is possible (Harel et al 2006).…”
Section: Discussionsupporting
confidence: 87%
“…The actions of NT3 are similar to those of other ovarian growth factors such as KL, LIF, BMP4, BMP7, KGF, PDGF, bFGF, and GDNF (Fortune 2003, Skinner 2005, Visser & Themmen 2005, Dole et al 2008. As research reveals more about the regulation of early follicle development, a picture is emerging of a complex network of paracrine and autocrine signaling factors that mediate communication between oocytes, granulosa cells, and surrounding thecal/interstitial cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A DNA microarray analysis conducted by Kawamura et al (2008) also identified Gdnf as an important ovarian transcript in the mouse, with follow-up experiments revealing that this factor is expressed by ovarian somatic cells, including cumulus, granulosa and theca cells (Kawamura et al 2008). In rats, Gdnf mRNA is present in the neonatal and adult ovary (Choi-Lundberg & Bohn 1995, Trupp et al 1995, and in the ovaries of newborns, GDNF protein localizes to the cytoplasm of oocytes in follicles representing all developmental stages, and to cumulus, granulosa and theca cells within antral follicles (Dole et al 2008).…”
Section: Expression Of Neurotrophic Factors In the Postnatal Ovarymentioning
confidence: 99%
“…The effects of neurotrophins on developing ovarian follicles have been investigated in the context of follicular survival, assembly and growth (Paredes et al 2004, Dole et al 2008, Dissen et al 2009, Kerr et al 2009, Dorfman et al 2011 and have been reviewed elsewhere (Ojeda et al 2000). However, studies investigating their role in antral follicles during the final stage of folliculogenesis, marked by oocyte maturation and the resumption of meiosis, which is concomitant with extrusion of the first polar body, as well as developmental competence of the early embryo, have not been reviewed in detail.…”
Section: Introductionmentioning
confidence: 99%